The Use Of Poetry By Imam Al Khatabi In The Service Of Ḥadith Texts: Maʿalim Al-Sunan As A Model/ توظيف الشعر عند الإمام الخطابي في خدمة النص الحديثي معالم السُّنن نموذجاً - Isa, Najmeddın (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores the use of Arabic poetry by the linguistic scholar al-Khaṭṭābī in his commentary on Sunan Abī Dāwūd, entitled Maʿālim al-Sunan, through an analytical examination of the poetic citations he employed to interpret rare Arabic expressions and explain the precise linguistic meanings of Prophetic hadiths. Al-Khaṭṭābī was distinguished by his combination of jurisprudence and hadith studies on the one hand, and linguistic and rhetorical analysis on the other, making him an early model of interdisciplinary integration between the Islamic sciences and the Arabic language. The importance of the topic lies in revealing the function of Arabic poetry in serving the hadith text as a scholarly tool that helps establish understanding and bring meanings closer, in addition to shedding light on an aspect that has rarely been studied: the systematic interaction between Arabic literature and hadith. The choice of this topic came in response to a gap in studies concerned with the use of poetry in hadith commentary, highlighting al-Khaṭṭābī’s role as a link between the religious and linguistic sciences. The research problem is framed in the question: How did Imām al-Khaṭṭābī employ Arabic poetry in the service of hadith commentary in Maʿālim al-Sunan? And to what extent did this usage contribute to interpreting expressions and clarifying legal and linguistic meanings? The study relied on the textual-analytical method to analyze the poetic citations, the descriptive method to present and explain them, and the inductive method to trace the patterns of their usage and extract the features of the process followed by al-Khaṭṭābī. The research aims to clarify the methodology adopted by al-Khaṭṭābī in incorporating poetic evidence, analyze the role of poetry in interpreting obscure terms, uncover the relationship between literary and jurisprudential knowledge, and highlight classical Arabic poetry as a tool for understanding the Sunnah. The study concluded that al-Khaṭṭābī employed Arabic poetry—which is considered the primary source of the Arabic language—with scholarly precision tied to context and meaning, contributing to the clarification of ambiguous meanings, the explanation of subtle lexical differences, and the connection of hadith meanings to their linguistic roots.